Exploring the richness of knowledge and culture: a journey through a research conference in Kyoto, Japan / Zafirah Liyana Abdullah and Siti Azma Jusoh - Abdullah, Zafirah Liyana; Jusoh, Siti Azma (Faculty of Pharmacy, 2024)
The experience of attending International Conference of Bioscience, Biochemistry and Bioinformatics 2024 (ICBBB 2024) that took place in Kyoto University, from Jan 12 -15, 2024 offers numerous opportunities to enhance our professional knowledge, expand our professional network, and immerse ourselves in a new cultural experience.